The Journey of St. Bonaventura - Sodeika, Tomas (Religija ir kultūra, 2011)
In the fall of 1259 St. Bonaventure arrived on Mount La Verna in Tuscany. As he ruminated on the stigmatized flesh of Francis of Assisi, he composed the Itinerarium mentis in Deum. According to Bonaventure the exterior sensible world contains “vestiges” of the divine, the interior world of the human soul contains “images” of the divine and, through the work of grace, the “names” of the divine become likenesses of it which raise the soul above itself. The essay explores how such triple mediation of the divine joint with the dichotomy of the in the medium and through the medium shape the six-fold way leading the human mind to the unity with God.